2012
DOI: 10.1128/aac.00643-12
|View full text |Cite
|
Sign up to set email alerts
|

Corifungin, a New Drug Lead against Naegleria, Identified from a High-Throughput Screen

Abstract: c Primary amebic meningoencephalitis (PAM) is a rapidly fatal infection caused by the free-living ameba Naegleria fowleri. The drug of choice in treating PAM is the antifungal antibiotic amphotericin B, but its use is associated with severe adverse effects. Moreover, few patients treated with amphotericin B have survived PAM. Therefore, fast-acting and efficient drugs are urgently needed for the treatment of PAM. To facilitate drug screening for this pathogen, an automated, high-throughput screening methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 36 publications
4
63
0
Order By: Relevance
“…Therefore, a drug that would be amebicidal and cysticidal and that could cross the blood-brain barrier would be optimal for the treatment of Acanthamoeba infection. We evaluated the polyene macrolide corifungin versus Acanthamoeba because an earlier study showed that it effectively killed another free-living ameba, Naegleria fowleri, with better efficacy than amphotericin B (24). Previous studies reported that a combination of amphotericin B and a second drug was effective in eradicating a skin infection and GAE caused by Acanthamoeba (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a drug that would be amebicidal and cysticidal and that could cross the blood-brain barrier would be optimal for the treatment of Acanthamoeba infection. We evaluated the polyene macrolide corifungin versus Acanthamoeba because an earlier study showed that it effectively killed another free-living ameba, Naegleria fowleri, with better efficacy than amphotericin B (24). Previous studies reported that a combination of amphotericin B and a second drug was effective in eradicating a skin infection and GAE caused by Acanthamoeba (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Trophozoites were harvested in logarithmic growth phase, usually 48 h after subculture, by chilling at 4°C and concentrated by centrifugation for 5 min at 300 ϫ g. In vitro studies of corifungin against A. castellanii trophozoites. To determine the effect of corifungin on the growth of A. castellanii trophozoites, 5 ϫ 10 5 amebae were incubated with 25 M, 100 M, and 200 M corifungin for 24, 48, 72, 96, and 120 h. Control trophozoites were incubated with fresh medium only. Cell numbers were calculated by hemocytometer at the end of incubation.…”
Section: Maintenance Of Acanthamoeba Castellaniimentioning
confidence: 99%
“…Initial reports for the in vivo efficacy of corifungin in a mouse model of PAM showed activity superior to that of amphotericin B at equivalent dosing (18). Chemically, corifungin is the sodium salt of amphotericin B with excellent aqueous solubility (Ͼ100 mg/ml) (18). The increased solubility of corifungin is likely to account for the described increase in activity.…”
Section: Amphotericin Bmentioning
confidence: 99%
“…Many of the problems with amphotericin B can be linked to its lack of aqueous solubility, which affects dissolution, compartmental concentration, and clearance. Recently, corifungin, which is described as a new drug entity, was granted orphan drug status for the treatment of PAM (18). Initial reports for the in vivo efficacy of corifungin in a mouse model of PAM showed activity superior to that of amphotericin B at equivalent dosing (18).…”
Section: Amphotericin Bmentioning
confidence: 99%
See 1 more Smart Citation